Empowering and Improving the Quality of Potential Village Resources in Candiwates - Ambarwati, Rita; Alif , Wildan; Octhavia , Ristha; Wijayanti , Putri Nur Rizki (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2024)
Community service projects in Candiwates Village, Prigen District, were carried out by academics from the Universitas Muhammadiyah Sidoarjo in partnership with the village authority and the cultural office. Exploring the potential of existing resources and long-term community empowerment were critical components in developing the work program for Candiwates Village. The renovation of the Candi Jawi cultural heritage site is one of the activity projects, and the results of this renovation will be utilized to develop facilities contained in the cultural heritage. The method of implementing this community service activity includes the stages of pre-implementation, implementation and evaluation. In addition to promoting the Sapta Pesona features of tourist villages, this community service activity includes socio-cultural, educational, and economic initiatives. This task was completed for one month, beginning on January 16, 2023, and ending on February 16, 2023. The implycations of this community service activity can increase community awareness and cooperation in realizing the development of an advanced and highly competitive tourist village in an integrated manner from the perspective of economic and socio-cultural aspects and educational considerations.